Optimize task distribution in grid computing - Shikder, Shyen Muhabbat; Uddin, Mahtab (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2008.